Theses information system of the postgraduate school, university of Ibadan (1997)
This study analysed the existing theses information storage and retrieval system of the Postgraduate School, University of Ibadan during the period of study (1994-96). It examined the factors that affected the effectiveness and efficiency of the system and with the intention of deriving some guidance for the design of an efficient theses information storage and retrieval system for the Postgraduate School. A computerized information system was found to be more suitable than the manual information system, as it was more efficient, and hence was recommended for use.